2018
DOI: 10.4028/www.scientific.net/msf.924.273
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inhomogeneity in Thermal Oxide SiO<sub>2</sub> Films on 4H-SiC Epitaxial Substrates by a Combination of Fourier Transform Infrared Spectroscopy and Cathodoluminescence Spectroscopy

Abstract: We measured Fourier transform infrared (FT-IR) and cathodoluminescence (CL) spectra of SiO2 films with a various thickness, grown on 4H-SiC substrates. The peak frequency of the transverse optical (TO) phonon mode was blue-shifted by about 5 cm−1 as the oxide-layer thickness decreased from 50-60 nm to 10 nm. The blue shift of the TO mode is considerd to be caused by interfacial compressive stresses in the oxide-layer. On the other hand, the TO phonon mode was found to dramatically decrease as the oxide-layer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
3
4
0
Order By: Relevance
“…Hirai and Kita 25 measured FT-IR spectra for thermal oxides on 4H-SiC (0001) Si and C faces and reported that the peak frequency of TO phonons remains nearly constant for thicker oxides (5–30 nm thick); this result is only slightly different from that reported by the authors, which agrees well with that reported by Seki et al. 26 In an extant study, 6 using a two-plate model comprising a thin SiO 2 layer on a 4H-SiC epitaxial layer, the authors suggested that the observed blueshift could be ascribed to a compressive stress of approximately 0.44 GPa induced across the SiO 2 –SiC interface.
Figure 6.Change in TO-phonon frequency for samples 1 and 2 as a function of oxide-layer thickness.
…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Hirai and Kita 25 measured FT-IR spectra for thermal oxides on 4H-SiC (0001) Si and C faces and reported that the peak frequency of TO phonons remains nearly constant for thicker oxides (5–30 nm thick); this result is only slightly different from that reported by the authors, which agrees well with that reported by Seki et al. 26 In an extant study, 6 using a two-plate model comprising a thin SiO 2 layer on a 4H-SiC epitaxial layer, the authors suggested that the observed blueshift could be ascribed to a compressive stress of approximately 0.44 GPa induced across the SiO 2 –SiC interface.
Figure 6.Change in TO-phonon frequency for samples 1 and 2 as a function of oxide-layer thickness.
…”
Section: Resultssupporting
confidence: 79%
“…Our model is supported by the increase of CL intensity, ascribed to OVCs in Yoshikawa et al. 6 We believe that the tensile stress in the SiO 2 /4H-SiC interface, greater than that in the SiO 2 /Si interface, is one of factors that D it and Q eff in the SiO 2 /4H-SiC interface are one to two orders of magnitude higher than those in the SiO 2 /Si interface.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations